(untitled) (Revista Brasileira de Computação Aplicada, 2014)
This work presents an introduction to Information Extraction systems and a survey of the known approaches of Information Extraction in the legal area. This work analyzes with particular attention the techniques that rely on the representation of legal knowledge as a means to achieve better performance, with emphasis on those techniques including ontologies and linguistic support. Some details of the systems implementations are presented, followed by an analysis of the positive and negative points of each approach, aiming to bring the reader a critical position regarding the solutions studied.